Fotogrametria, polityka i przedsiębiorczość a inwentaryzacja zabytków. Albrecht Meydenbauer w Poznańskiem w roku 1885 i 1887 - Wojdak, Ewelina (Artium Quaestiones, 2019)
A standard belief as regards the conservation of architectural monuments in the 19thcentury is that the very idea of conservation was commonly accepted, while the monuments of the past were used to promote national identity. On the other hand, photography is also commonly considered a technology that was naturally predisposed to popularize those monuments and/or appropriate them as symbols. For those reasons, the photogrammetric documentation of some buildings from the region of Poznań, made by Albrecht Meydenbauer commissioned to do it by the Prussian government, could be classified as combination of conservation and nationalism, “typical” of the late 19thcentury. However, the author proposes another interpretation and claims that such events were not necessarily “realizations” of “widespread” ideas of identity building. Referring to the generative model of identity building developed by Friedrik Barth, she analyzes how specific situations and meanings were gradually generated through the interaction of actors who attempted to reach their goals and values by available means. The introduction and popularization of Meydenbauer’s invention is presented in the paper with reference to Bruno Latour’s research on the development and implementation of innovations in science. In such a context, photogrammetry turns out to have been a result of seeking support by business, i.e. the mobilization of resources, while the national discourse was used for that purpose as one of the available means.